The Relationship Between Physical Activity and Wellbeing Among Adolescent Girls During Menstruation (Baltic Journal of Sport and Health Sciences, 2026)
Purpose: Menstruation can significantly impact adolescent girls’ physical and psychological wellbeing, yet the influence of physical activity on their experiences during this period remains insufficiently understood. The objective of this study was to evaluate the association between physical activity and wellbeing among adolescent girls during menstruation.Methods: A cross-sectional design was used, involving 431 female students in grades 9 through 12, aged 15 to 19 years (standard deviation = 1.08). Data were collected via an online survey. The questionnaire was based on the “Surveillance of water, sanitation and hygiene in schools: A practical tool” (World Health Organization, 2019).Results: The main reason for school absenteeism during menstruation was painful menstruation (92.4%). During menstruation, 55.1% of girls reported feeling bad or very bad, whereas only 8.6% indicated feeling good or very good. Regarding participation in physical education classes during menstruation, 24.6% of girls reported active participation, while almost half (47.2%) stated that their teachers permitted them to observe rather than participate.In terms of extracurricular physical activity, 39.4% of girls engaged in leisure-time physical activity, and 37% attended after-school sports activities for periods ranging from one year to five years or more. Girls with longer durations of after-school sports activities were significantly less likely to miss sports activity during menstruation, χ² (10, n = 460) = 18.711, p = 0.044. However, there was no significant association between years of training and wellbeing during menstruation (p = 0.759).Furthermore, more than half of the participants reported feeling bad or very bad during menstruation, regardless of their engagement in after-school sports activities (p = 0.905).Conclusion: Menstrual pain is the primary factor contributing to school absenteeism among adolescent girls during menstruation. Only a minority participate in physical education classes during this period, with most either observing or abstaining from attendance. Girls with extended training experience are less likely to miss sports activity during menstruation, even when experiencing discomfort. Nevertheless, there is no significant relationship between physical activity levels and self-reported wellbeing during menstruation.